KEMAMPUAN CERNA PROTEIN DAN ENERGI METABOLISME PERKICI PELANGI TRICHOGLOSSUS HAEMATODUS - Rachmatika, Rini; Sari, Andri Permata (Perhimpunan Biologi Indonesia, 2015)
ABSTRACTProtein is one of the important aspects in animal feed to fulfill basic needs and stimulate reproduction behaviors. The aims of this research were to determine food preferences and observe digestibility of protein in rainbow lorikeet. This research consisted of two experiments, which were 1 week of preliminary study and 4 weeks for data collection. Studies were carried out using two 4-month-aged rainbow lorikeets (Trichoglossus haematodus). The birds were kept individually in metabolism cage (86 x 42 x 53 cm) and treated with 5 different protein sources consisting quail?s egg (A), soybean meal (B), koi fish pellet (C), milk 7% (D), and milk 13% (E). The diets were then offered to the birds ad libitum in the form of mashes, and sweet corn served separately. Variables observed include dry matter consumption, apparent metabolizable energy value, and apparent digestibility of protein value. Feed intake of soybean meal mashes was higher than the others. From the calculation, AME of milk 7% mashes was the highest (49.27 cal/g), and AME of soybean meal mashes was the lowest (38.07 cal/g). ADP of soybean meal mashes was highest (87.88 %) compared to the others. Keywords: rainbow lorikeet, apparent metabolizable energy, apparent digestibility protein